Interspecific hybridization of potato: theoretical and applied aspects - T. A. Gavrilenko; A. P. Yermishin (Вавиловский журнал генетики и селекции)
The common potato Solanum tuberosum is the fourth most important crop in the world and like many other cultivated plants is characterized by low level of genetic diversity. The most effective approach to broaden genetic diversity of breeding varieties is based on the introgression of genetic material of wild and cultivated species belonging to section Petota Dumort. of the genus Solanum L. This section, according to estimates by different taxonomists, includes from 112 to 235 species. At the same time, because of the barriers of prezygotic and postzygotic incompatibility, only about 10 % of wild potato species have been actively involved into the breeding process and their genetic material has been introgressed into the gene pool of varieties. To date, molecular genetics, genomics, and biotechnology have accumulated a large amount of information, allowing the problems of extension of the genetic diversity of common potato to be addressed. The article presents a review of modern data about the genetic factors determining prezygotic and postzygotic incompatibility, about the features of involvement in the hybridization process of the self-compatible and self-incompatible species of section Petota and species with different values of the endosperm balance number (EBN), as well as possible mechanisms of interaction between the parental genomes during the formation of the endosperm of the hybrid seed. Data are provided on the value of the theory of EBN for the further development of applied research aimed at increasing the genetic diversity of the breeding gene pool. This review discusses the traditional and modern approaches and methods of overcoming interspecific incompatibility and gives examples of successful studies on introgressive hybridization of potato. The article is preceded by information about the genetic diversity of potato species belonging to section Petota of the genus Solanum.